A 6-year study on the mortality dynamics of sprouts germinated on Schima superba after a severe ice storm in southern China - Cao, Yonghui; Zhou, Benzhi; Wang, Xiaoming (Frontiers in Plant Science, 2023)
Natural disturbances modify forest structure by affecting regeneration dynamics and can change main ecosystem functions. An unexpected heavy ice storm occurred in southern China in early 2008 caused extensive damage to forests. Resprouting of woody plants in a subtropical forest has received a little attention. To assess the role of the survival time and mortality dynamics of new sprouts in forest restoration after an ice storm, damage types, an annual number and mortality rates of sprouts for all tagged and sampled resprouted S.superba individuals more than or equal to 4 cm in basal diameter (BD) in six permanent monitoring plots (20 m×20 m) were surveyed for 6 consecutive years, in a subtropical secondary forest dominated by S.superba in Jianglang Mountain, China. Results showed that the damage type was related to a tree size. Large individuals with basal diameter larger than 13.0 cm were prone to decapitation, while small individuals with BD ˂10.0 cm were prone to stem-broken and bending. For different damage types of individuals, the new sprouts boomed in each year after the ice storm had an increasing mortality rate over the recovery. A higher mortality rate appeared earlier for new sprouts those germinated in the later years. Those new sprouts germinated in 2008 had a more exuberant vitality, and survive longer. The proportion of decapitated trees surviving for 6 years was much higher than that of uprooted and leaning trees. Sprouts could survive for 6 years for those germinated near trunk bases of uprooted trees and those near the upper trunks of decapitated trees. There is a linear or nonlinear correlation between the accumulative mortality rate of new sprouts and the average diameter of new sprouts boomed in each year after ice storm during the recovery, and this relationship is affected by different damage types. Under climate change, these results had important implications for construction of branch sprout dynamic model and will help guide forest management and restoration strategies to select sprouts harvesting methods and time and that will limit the effects of damaged types and trunk position on sprout regeneration after the disturbance like ice storm.